Internet Banking Tools and Client Satisfaction with Nepalese Commercial Banks - Sharma Gaire, Amrit Kumar (Journal of Nepalese Management and Research, 2023)
The principal aim of this research endeavor was to assess the influence of Internet tools on client satisfaction within the commercial banking sector in Surkhet. The independent variables, namely Internet banking (IB), mobile banking (MB), automated teller machine (ATM), and point of sales (POS), were selected for this investigation, with client satisfaction designated as the dependent variable. Employing a descriptive research design and quantitative data, the study utilized a convenience sampling technique and administered a structured questionnaire to collect relevant data from respondents. The sample comprised 101 Internet banking users selected from the pool of Internet banking users in Surkhet. In the process of data analysis, various statistical measures, including frequency, mean, standard deviation, univariate, bivariate, and multivariate regression, were employed. The study’s findings revealed a noteworthy positive impact of Internet banking tools on client satisfaction. This implies that commercial banks’ integration and utilization of Internet banking tools in Surkhet are associated with a statistically significant improvement in client satisfaction.